SITUATION AWARENESS DAN KONSEP PERSEPSI PROFESIONAL PEMBERI ASUHAN: A LITERATURE REVIEW - Putu Ari Sukriyanti (Jurusan Keperawatan Poltekkes Kemenkes Makassar, 2019)
Situation Awareness (SA) is acknowledged as the most important factor in intensive care unit and SA as nursing strategy in improving deterioration risk identification. To date, there is no SA review with regard to mitigation and deterioration risk escalation and how healthcare providers’ perception about SA associated with deteriorating risk, an evidence-based is required. Objectives: To report analysis result regarding SA associated with mitigation and risk escalation as well as healthcare providers’ perception about SA associated with deteriorating risk.. Methods: This article is comprised of full text quantitative and qualitative studies in 2008-2018 which fulfill PICO and SPIDER criteria. Browsing was conducted in multiple data base namely PubMed, Proquest, Google Scholar, and Science Direct with keywords “Situation Awareness” or “Non Technical Skill” and “Intensive Care”as well as “Deterioration”. Articles were selected using Appraisal tool PRISMA resulted in 14 articles. Result: the SA in nursing is defined in three levels. Error or delayed which occurs in any level will influence the result of identification process hence affect the mitigation and risk escalation processes. There is a discrepancy regarding SA concept in operating room team. Eventhough SA is described in difference subcategories, broadly speaking, these differences are still in line with the three levels of SA, namely perception on information, comprehension, and projection. Conclusion: the good SA will increase team awareness on the change in patient’s condition so that deterioration is recognized as early as possible. The difference in perception regarding SA will bring about negative impact on patient safety hence it is imperative to figure out nurse perception in order to achieve and sustain SA in PICU. Keywords: Deterioration, Intensif Care, Non Technical Skill, and Situation Awareness